An elemental S/P photocatalyst for hydrogen evolution from water under visible to near-infrared light irradiation. Issue 87 (16th October 2019) - Cao, Qiuyan; Guo, Minna; Cao, Jing; Lin, Haili; Chen, Yong; Chen, Shifu
Abstract : An elemental S/P photocatalyst exhibits enhanced photocatalytic activity for hydrogen evolution from water due to the co-catalyst effect of S. Abstract : A novel elemental S/P photocatalyst exhibits enhanced photocatalytic activity for hydrogen evolution from water due to the co-catalyst effect of S, when irradiated with visible to near-infrared light.